RESPIRATORY AND CIRCULATORY PROBLEMS OF COVID-19 IN THE CONTEXT OF ESTABLISHING INTENSIVE CARE UNIT NURSING DIAGNOSIS - Ika Ainur Rofi'ah; Muhammad Sajidin (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
Introduction: The novel coronavirus disease 2019 (COVID-19) is a virus that attacks the respiratory tract with rapid spread and high mortality. Initial reports that COVID-19 associated with critical care due to the severity of the disease requiring mechanical assistive devices in its treatment. The purpose to identify the nursing diagnosis related to respiratory and circulatory problems of COVID-19 in the critical care unit. Method: An integrative review highlights the issue that nursing problems related to respiratory and circulatory in COVID-19 patients admitted to the Intensive Care Unit (ICU). This study focuses on papers published from 2020 to 2021 using the keyword